Surfactant properties and emulsifying activity of the gum exudate of Prosopis juliflora (Sw.) DC. - Rincón-Acosta, Fernando; Félix López, Miryam; Hurtado, Ernesto; Guerrero-Castillo, Rocío; Beltrán, Olga (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Gums exudates are macromolecules consisting of carbohydrates (majority fraction), proteins and lipids (minority fraction), with variable concentrations of minerals, polyphenols, flavonoids, tannins and other bioactive phytochemical compounds. These natural products are used as emulsifying agents in multiple industries. The surfactant properties of a new source of gum exudate produced by Prosopis juliflora (Sw.) DC. were evaluated. Additionally, water-oil dispersions prepared with this natural polymer were tested for their emulsifying capacity and stability. A Du Noüy ring tensiometer was used to determine the amphipathic behavior of the investigated gum. The gum exudate of P. juliflora tested at 0.5 % m/v, decreases the values of surface tension (49.35 dyne.cm-1) and interfacial tension (12.78 dyne.cm-1), which evidences the potential emulsifying activity (EA) of this polysaccharide. EA values of 95 % and emulsion stability of 95.8 % were obtained, suggesting that P. juliflora gum contributes to improve the capacity and speed of adsorption of molecules between the dispersed phase and continues to form a stable emulsion. The surfactant and emulsifying activity of the investigated gum is associated with the high protein content (16.89 %) and the presence of methyl groups in its structure. Therefore, the gum exudate of P. juliflora constitutes a promising source of hydrocolloids as an emulsifier that could be evaluated in the manufacture of pharmaceuticals, food and even cosmetics. Additionally, it constitutes an unexploited natural resource that would contribute to the development of the South American regional economies where this species grows.